Exercising the Role and Authority of Indonesia's Senate: Implications of Constitutional Court Decision 92/PUU-X/2012 - Kafandi, Muhammad Afif; Setiadi, Wicipto; Thohari, Ahmad Ahsin (Research Horizon, 2024)
The Regional Representative Council (Dewan Perwakilan Daerah/DPD) in Indonesia is a legislative body that reflects the country's bicameral system, which includes two chambers. However, the DPD’s authority is notably weaker than that of the House of Representatives (Dewan Perwakilan Rakyat/DPR), leading to what is often described as "soft bicameralism" in Indonesia. This study explores the role and authority of the DPD following the Constitutional Court Decision Number 92/PUU-X/2012, which addressed the DPD's function within the legislative process. The research adopts a normative approach, focusing on legal norms from the 1945 Constitution and related legislation, alongside a statutory and historical analysis. This includes examining relevant laws, such as Law Number 17 of 2014 and the DPR's 2014 Rules of Procedure, which incorporate the Constitutional Court's decision. This decision essentially introduced a tripartite legislative model involving the DPR, DPD, and the President, providing the DPD a role in Level I discussions. In Level II discussions, the DPD presents its opinions during plenary sessions before a bill’s approval between the DPR and the President. However, the DPD remains excluded from the final ratification. Strengthening the DPD's legislative authority requires a fifth constitutional amendment to enhance its role or a willingness by the DPR to share legislative responsibilities, thereby establishing a stronger checks and balances system.